Design and Development of a Thermal Management System for Tablets: A Smart Cover Approach to Enhance Safety and Performance - Ghaderi, Mehrdad; Akbarimajd, Adel; Bakhtiarian, Mehdi (International journal of industrial engineering and operational research, 2025)
The ubiquity of smartphones and tablets in our daily lives has resulted in an augmented demand for high-performance batteries. However, these batteries are susceptible to explosions due to negligent usage, atypical charging conditions, and overheating caused by battery-intensive applications. In response to this predicament, a novel study proposes the utilization of a "Smart Cover", which functions as a tablet cover capable of assessing and detecting the tablet's temperature. Furthermore, it incorporates a built-in temperature sensor that triggers an alarm when necessary. Additionally, the Smart Cover activates fans integrated within the tablet's cover to facilitate cooling. The design of the cover was achieved through the utilization of 3D design AutoCAD, while an electrical circuit was employed to safeguard tablets against ignition and battery explosions. The research methodology employed in this article is classified as "Modeling and Simulation."From an operational research perspective, ensuring device safety while maintaining performance efficiency is a critical challenge. This study explores the design and effectiveness of smart tablet covers in heat dissipation and explosion prevention, aligning with industrial engineering applications in product safety and reliability.